Street art et mise en tourisme de la métropole parisienne, des festivals aux street art tours - Sophie Blanchard; Romain Talamoni (EchoGéo)
In the Parisian metropolis, street art is becoming a touristic object. It started with festivals and art exhibitions, followed by an increasing number of guided street art tours, in Paris and the suburbs. The private actors who organize these street art tours try to reach a very large audience, from curious locals to international tourists, and use mainly the internet for their promotion, via independent sites as well as major ones like Airbnb. Street art tours participate in the touristification of gentrified or renovated areas, therefore taking part in the intertwined power relations of urban society.